Biotechnological Advances on Mariculture in Costa Rica. A Review of the Investigation Developed by the School of Biological Sciences of the National University - Rojas-Alfaro, Rebeca (2017)
The development of mariculture in Costa Rica has required validation, innovation and generation of scientific-biotechnological knowledge. A revision of the main biotechnological advances on mariculture that have been applied and developed by the School of Biological Sciences of the National University of Costa Rica is presented. Experimentation and optimization of culture technology have boosted Crassostrea gigas oyster farming in the country and the establishment of local enterprises. Scientific research has generated globally significant biotechnological advances on the reproductive biology of penaeid shrimp and has allowed the controlled reproduction of commercial marine fish in the Gulf of Nicoya, Costa Rica. In addition, biotechnological techniques have been implemented and evaluated for growing algae, bacterial depuration of molluscs, Harmful Algal Blooms monitoring and bioremediation. Biotechnology research on mariculture and the transfer of new biotechnologies must be promoted and protected by the Intellectual Property of biotechnological innovations as tools for economic and social development in Costa Rica.